2010
DOI: 10.24084/repqj08.555
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Power Quality in Health Care Facility

Abstract: Abstract. Modern healthcare facility has unique power system requirements as the power quality and reliability is a crucial feature to maintain the critical services such as surgical operations, intensive care units and other critical services. Healthcare facility has become dependent on the quality of electrical supply. This paper aims at assessing the level of harmonic pollution to a health care facility. The investigation focus on assessing the level of THD on this healthcare facilitates.Further discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Figure 1 presents the curve of current variation in the neutral wire of the network for external lighting of the trading and entertainment center in the city of Krasnoyarsk [14]. The harmonics cause malfunction of circuit breakers because of a high value of the cross ratio, transformer overheating because of additional eddy current losses, capacitor damage because of high values of harmonic currents, increase losses in the asynchronous motors, create transient overvoltages in the cosine capacitors, lead to malfunction of protection and automation systems and many other adverse effects [15][16][17]. The costs induced by harmonics amount to 5.4 % of all the costs due to poor power quality [10].…”
Section: Examples Of the Adverse Impact Of Poor Quality Voltagementioning
confidence: 99%
“…Figure 1 presents the curve of current variation in the neutral wire of the network for external lighting of the trading and entertainment center in the city of Krasnoyarsk [14]. The harmonics cause malfunction of circuit breakers because of a high value of the cross ratio, transformer overheating because of additional eddy current losses, capacitor damage because of high values of harmonic currents, increase losses in the asynchronous motors, create transient overvoltages in the cosine capacitors, lead to malfunction of protection and automation systems and many other adverse effects [15][16][17]. The costs induced by harmonics amount to 5.4 % of all the costs due to poor power quality [10].…”
Section: Examples Of the Adverse Impact Of Poor Quality Voltagementioning
confidence: 99%
“…HE performance of the matrix converter topology has been widely discussed and different approaches have been proposed to determine the proper control strategy [1][2][3], [10][11][12], [14]. The relatively small reactive component in the DC link is one of the significant advantages of the matrix converters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown the possibility to obtain balanced and sinusoidal output voltages even if the input voltages are unbalanced [4]- [7]. It has also been shown that the power disturbance of this kind will disturb the critical services such is in a healthcare facility and/or hospital [10][11]. By using proper modulation strategies, it is possible to reduce or to eliminate up to the significant level the input current harmonics under unbalanced supply voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [7] show the measurements of harmonics generated by energy saving lamps. The paper [8] presents the level of harmonics measured in the medical center and their negative impact on the operation of medical equipment. In [9] the authors show the results of large-scale measurements of power quality indices in the 110 kV networks of Siberia.…”
Section: Introductionmentioning
confidence: 99%